Biotechnological aspects in the in vitro propagation of magnoliaceae (2022)
The Magnoliacea family is made up of 352 species, of which about 70% are in some category of threat. In Colombia, the greatest diversity of Magnolias in the Neotropics is concentrated with 39 species, of which 29 are exclusive to the country and 95% have some category of threat of extinction, mainly due to the fragmentation and degradation of habitats, geographic distribution restricted, small and isolated populations, unsustainable use of wood and difficulties of natural propagation. Plant biotechnology and in vitro tissue culture techniques are increasingly used as an effective alternative for the propagation of threatened species that deserve particular attention and conservation efforts. Worldwide, valuable efforts have been made to propagate species of the Magnoliaceae family through these biotechnological techniques, whether for ornamental, industrial, pharmacological or conservation purposes, with favorable results. For this reason, the objective of this review is to highlight the importance of the use of biotechnological processes, in this case micropropagation as an in vitro technique, in the propagation of species of the Magnoliaceae family, due to its importance at an ecological and conservation level.